Hearing Improvement after Myringoplasty in Sudanese Patients - Ali, Rasha; Ahmed, Sharfi; A, Abusefian; B, Mohamed (International Journal of Innovative Research in Medical Science, 2016)
Myringoplasty is a reconstructive operation of the tympanic membrane to prevent recurrent ear infection and improve the hearing. Objective: to assess the hearing improvement after myringoplasty and factors that might affect the outcome. Patients and methods: Fifty one patients who had undergone myringoplasty were taken on this prospective study. They were subjected to clinical and audiological examination by a questionnaire, and the results of pure tone audiogram were analyzed. Results: Most of the patients (51 %) were in the age group 0-20 years. Male to female ratio was 1:1.12. The common cause of perforation was chronic ear infection and its commonest size was subtotal (34 patients=66.7%). Most of the patients had conductive hearing loss (47 patients=92.2 %), while mixed hearing loss was found in 4 patients (7.8%). Postauricular approach was used in18 patients (35.3%) and had higher hearing threshold improvement (94.4%).Underlay technique and temporalis fascia graft both had a higher hearing threshold improvement. The overall hearing threshold improvement was 80.4% and air-bone gap had decreased in 80.4%. Conclusion and recommendations: in this study myringoplasty was mainly performed in young age, had best hearing threshold improvement and better outcome in female, temporalis fascia, underlay technique and postauricular approach. We recommend for further studies conducted with more number of patients and long-time follow up after myringoplasty for assessment of hearing improvement.